2019
DOI: 10.5080/u23613
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder Symptoms and Their Predictors in Earthquake or Fire Survivors

Abstract: ÖZET Amaç: Bu çalışmada deprem ve/veya yangın deneyimleyenlerde olay öncesi sahip olunan acil durum bilgisi, olay üzerindeki kontrol algısı, algılanan tehdit ve olay sırasında deneyimlenen bedensel belirtilerin travmatik stres belirtileri ile ilişkisini incelemek amaçlanmıştır.Yöntem: Araştırma verileri 2009 yılı İzmir ili itfaiye verileri kullanılarak ev yangını deneyimlemiş kişilerden (n=92), Sağlık Grup Başkanlığı'na başvuran kişiler arasında 2005 yılı Seferihisar depremini deneyimlemiş kişilerden (n=38) ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It is known that the incidence of psychological problems and anxiety increases after earthquakes of this and similar magnitudes, resulting in great losses (6,7). It is stated that individuals who have experienced earthquakes display higher post-traumatic stress symptoms compared to those who have experienced other natural disasters (28). This actually indicates the magnitude of the negative impact of earthquakes on people among natural disasters.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that the incidence of psychological problems and anxiety increases after earthquakes of this and similar magnitudes, resulting in great losses (6,7). It is stated that individuals who have experienced earthquakes display higher post-traumatic stress symptoms compared to those who have experienced other natural disasters (28). This actually indicates the magnitude of the negative impact of earthquakes on people among natural disasters.…”
Section: Discussionmentioning
confidence: 98%
“…Experiencing fire and performing fire extinguishing duties using fire extinguishing equipment increased the fire attitude. In the study of Cankardaş and Sofuoğlu (2019), it was observed that having knowledge about self‐protection during the incident and what to do during the evacuation of people who experienced a fire contributed to the decrease in the perception of life threat and the increase in the perception of control.…”
Section: Discussionmentioning
confidence: 99%
“…After natural disasters, there is an increase in PTSD, major depressive disorder, sleep disorders, generalized anxiety disorder, substance use disorder, suicide, and grief reactions (1). PTSD, on the other hand, is one of the most frequently observed and studied mental health disorders together with natural disasters (26). Although natural disasters affect many people at the same time, according to the World Mental Health Survey, the prevalence of traumatic stress symptoms after a natural disaster is around 3.8% (27).…”
Section: Ptsd After Natural Disastersmentioning
confidence: 99%